2017
DOI: 10.1111/eci.12853
|View full text |Cite
|
Sign up to set email alerts
|

Dynamics of neutrophil gelatinase‐associated lipocalin plasma and cerebrospinal fluid concentrations in older males

Abstract: This study illustrates the temporal regulation of NGAL in plasma and CSF, which potentially is a useful reference for studies measuring NGAL as biomarker in older individuals.

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
1

Citation Types

0
1
0

Year Published

2019
2019
2021
2021

Publication Types

Select...
4

Relationship

0
4

Authors

Journals

citations
Cited by 4 publications
(1 citation statement)
references
References 32 publications
(55 reference statements)
0
1
0
Order By: Relevance
“…Serum samples were withdrawn at different hours during the day depending on clinic organization since previous study did not found any circadian influence on systemic LCL2 levels 27 . All patients had an active episode of CSCR at the time of blood sampling defined as the presence of subretinal fluid.…”
Section: Methodsmentioning
confidence: 99%
“…Serum samples were withdrawn at different hours during the day depending on clinic organization since previous study did not found any circadian influence on systemic LCL2 levels 27 . All patients had an active episode of CSCR at the time of blood sampling defined as the presence of subretinal fluid.…”
Section: Methodsmentioning
confidence: 99%